Patient Satisfaction After Adult Spinal Deformity Surgery Does Not Strongly Correlate With Health-Related Quality of Life Scores, Radiographic Parameters, or Occurrence of Complications. Issue 10 (15th May 2017) - Hamilton, David Kojo; Kong, Christopher; Hiratzka, Jayme; Contag, Alec G.; Ailon, Tamir; Line, Breton; Daniels, Alan; Smith, Justin S.; Passias, Peter; Protopsaltis, Themistocles; Sciubba, Daniel; Burton, Douglas; et al.
Abstract : Study Design: This is a multicenter retrospective review of prospectively collected cases. Objective: Our objective was to evaluate the relationship between patient satisfaction, health-related quality of life (HRQoL) scores, complications, and radiographic measures at 2 years postoperative follow-up. Summary of Background Data: For patients receiving operative management for adult spine deformity (ASD), the relationship between HRQoL measures, radiographic parameters, postoperative complications, and self-reported satisfaction remains unclear. Methods: Data from 248 patients across 11 centers within the United States who underwent thoracolumbar fusion for ASD and had a minimum of 2 years follow-up was collected. Pre- and postoperative scores were obtained from the Scoliosis Research Society 22-item (SRS-22r), the Oswestry Disability Index (ODI), the 36-Item Short Form Health Survey (SF-36), and the Visual Analogue Scale. Sagittal vertical axis, coronal C7 plumbline, lumbar lordosis, pelvic tilt, T1 pelvic angle, and the difference between pelvic incidence and lumbar lordosis were assessed using postoperative radiographic films. Satisfaction (SAT) was assessed using the SRS-22r; patients were categorized as highly satisfied (HS) or less satisfied (LS). The correlation between SAT and HRQoL scores, radiographic parameters, and complications was determined. Results: When compared with LS (n = 60) patients, HS (n = 188) patients demonstrated greater improvement in final ODI, SF-36 component scores, SRS-Total, and Visual Analogue Scale back scores ( P  < 0.05). The correlations between SAT and the final follow-up and 2 year change from baseline values were moderate for Mental Component Summary, Physical Component Summary, and ODI or weak for HRQoL scores ( P  < 0.0001). The HS and LS groups were equal in pre- or final postoperative radiographic parameters. Occurrence of complications had no effect on satisfaction. Conclusion: Among operatively treated ASD patients, satisfaction was moderately correlated with some HRQoL measures, and not with radiographic changes or postoperative complications. Other factors, such as patient expectations and relationship with the surgeon, may be stronger drivers of patient satisfaction. Level of Evidence : 3